PENERAPAN DESAIN THERAPEUTIC PADA WADAH KREATIF PEKERJA FILM ANIMASI PENGIDAP INSOMNIA - Canniago Hermindo; Suryono Herlambang (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The creative industry plays an important role in driving Indonesia's overall economic growth. Data released by the Central Bureau of Statistics (2018) shows that the creative economy sub-sector makes a significant contribution to the national economy by contributing 7.44% to the Gross Domestic Product (GDP). One of them comes from the film, animation, and video sub-sector. Based on the Creative Economy Agency (2020), the growth of this industry reaches 10% annually. However, this cannot be separated from the creative workers who often get insomnia due to work. Insomnia is a disorder in the form of difficulty getting to sleep, difficulty maintaining sleep, and sleep dissatisfaction. Based on the US Census Bureau, International Data Base in 2004 as many as 28.035 million people in Indonesia (11.7%) suffer from insomnia. This shows that insomnia has become a problem faced by the majority of Indonesian people. Rehabilitation for people with insomnia is needed because it can interfere with health and reduce productivity. Therefore, a creative workspace for animated film workers with insomnia is needed which aims to facilitate them in the work process as well as fill their time when experiencing the insomnia phase to support recovery so they can return to their productive activities. The research uses qualitative methods with library research followed by data collection through surveys of similar buildings and interviews with users regarding space requirements that support creative work processes and insomnia. Then the use of the healing therapeutic concept as a design criteria related to connectedness with nature, culture, privacy, physical comfort, multifunctional activities, relaxation rooms, interactive, flexible, and beautiful that aim to comfort users in assisting their work and recovery processes. Keywords: Creative; Insomnia; Therapeutic Abstrak Industri kreatif memainkan peran penting dalam mendorong pertumbuhan ekonomi Indonesia secara keseluruhan. Data yang dikeluarkan oleh Badan Pusat Statistik (2018) menunjukkan bahwa subsektor ekonomi kreatif berkontribusi signifikan terhadap perekonomian nasional dengan menyumbangkan sebesar 7,44% terhadap Produk Domestik Bruto (PDB). Salah satunya berasal dari sub sektor film, animasi, dan video. Berdasarkan Badan Ekonomi Kreatif (2020), pertumbuhan industri tersebut mencapai 10% tiap tahunnya. Namun hal tersebut tidak lepas dari pekerja kreatif tersebut yang sering terkena insomnia akibat pekerjaan. Insomnia merupakan gangguan berupa kesulitan untuk memulai tidur, kesulitan mempertahankan tidur, dan ketidakpuasan tidur. Berdasarkan US Census Bureau, International Data Base tahun 2004 sebanyak 28,035 juta jiwa penduduk Indonesia (11,7%) terjangkit insomnia. Hal tersebut menunjukan bahwa insomnia sudah menjadi masalah yang dihadapi mayoritas masyarakat Indonesia. Rehabilitasi bagi pengidap insomnia diperlukan karena dapat menggangu kesehatan dan menurunkan produktivitas. Oleh karena itu, diperlukan sebuah wadah kerja kreatif pekerja film animasi pengidap insomnia yang bertujuan memudahkan mereka dalam proses bekerja sekaligus mengisi waktu mereka ketika mengalami fase insomnia untuk menunjang pemulihan sehingga bisa kembali beraktivitas secara produktif. Penelitian menggunakan metode kualitatif dengan riset kepustakaan dilanjutkan dengan pengumpulan data melalui survei bangunan sejenis dan wawancara dengan user terkait kebutuhan ruang yang menunjang proses kerja kreatif dan insomnia. Kemudian penggunaan konsep healing therapeutic sebagai kriteria desain yang terkait keterhubungannya dengan alam, budaya, privasi, kenyamanan fisik, kegiatan multifungsional, ruang relaksasi, interaktif, fleksibel, dan indah yang bertujuan untuk kenyamanan pengguna dalam membantu proses kerja dan pemulihan mereka.